2021
DOI: 10.1002/chem.202102730
|View full text |Cite
|
Sign up to set email alerts
|

The E2 state of FeMoco: Hydride Formation versus Fe Reduction and a Mechanism for H2 Evolution

Abstract: The iron-molybdenum cofactor (FeMoco) is responsible for dinitrogen reduction in Mo nitrogenase. Unlike the resting state, E 0 , reduced states of FeMoco are much less well characterized. The E 2 state has been proposed to contain a hydride but direct spectroscopic evidence is still lacking. The E 2 state can, however, relax back the E 0 state via a H 2 sidereaction, implying a hydride intermediate prior to H 2 formation. This E 2 !E 0 pathway is one of the primary mechanisms for H 2 formation under low-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 86 publications
2
62
4
Order By: Relevance
“… a We emphasize that the disposition of the hydrides, is a matter of much discussion (for example, ref explicitly addresses this question). …”
Section: Discussionmentioning
confidence: 99%
“… a We emphasize that the disposition of the hydrides, is a matter of much discussion (for example, ref explicitly addresses this question). …”
Section: Discussionmentioning
confidence: 99%
“…In the E 1 state, FeMoco has an even number of electrons, but the spin stateeither diamagnetic or integer spinis currently unknown. It has recently been proposed based on QM/MM calculations that the Fe part of the Mo cubane is reduced in the E 1 state compared to the E 0 state. , Additionally, multiple computational studies have proposed the belt sulfide S2B or S5A being protonated in the E 1 state. , In the E 2 state, FeMoco exhibits two distinct S = 3/2 EPR signals ( g = [4.21, 3.76, 1.97]/[4.69, 3.20, 2]). Computational models have suggested that hydride formation can occur in this redox state. ,,, …”
Section: Introductionmentioning
confidence: 93%
“…26−29 Computational models have suggested that hydride formation can occur in this redox state. 22,24,29,30 The presence of CO does not alter the E 0 EPR signal of the MoFe protein, which suggests no interaction between CO and FeMoco in the wild-type resting state MoFe protein. However, under turnover conditions, the presence of CO generates two characteristic S = 1/2 EPR signals: loCO EPR and hiCO EPR , that arise under low and high CO pressures, respectively (g = [2.09, 1.97, 1.93]/[2.17, 2.06], labeled lo-CO/hi-CO in the original work).…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A fit of eq 11 to k NHd 3 versus PH 2 with obtained k HPd 4 /k re and k AP parameters gives k oa = 5.5 ± 0.2 atm −1 H 2 s −1 (Figure 4B) ) and confirms that this process is relatively slow and easily outcompeted with sufficient k ea , a result in agreement with recent computational studies. 28 Second, once E 4 (4H) is achieved, H 2 evolution independent of N 2 binding proceeds with a rate constant, k HPd 4 , much higher than that for k HPd 2 . H 2 formation with k HPd 4 competes with N 2 binding with a competition parameter k HPd 4 /k re = 1 (atm N 2 ) (0.6 ± 0.1 (mM N 2 )).…”
Section: ■ Introductionmentioning
confidence: 99%